1998
DOI: 10.1046/j.1471-4159.1998.70062286.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid‐Dependent Action of Neural Crest Factor AP‐2: Stimulation of Phenylethanolamine N‐Methyltransferase Gene Expression

Abstract: AP‐2 is a vertebrate transcription factor expressed in neural crest cells and their derivative tissues, including the adrenal medulla, where epinephrine is produced. AP‐2 is shown to stimulate expression of the gene encoding the epinephrine biosynthetic enzyme phenylethanolamine N‐methyltransferase (PNMT). However, stimulation of the PNMT gene by AP‐2 requires glucocorticoids and appears to be mediated through the interaction of AP‐2 with activated type II glucocorticoid receptors. Mutation of AP‐2 and/or gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…This concurs with studies that have revealed low levels of PNMT mRNA expression in human phaeochromocytoma (Isobe et al 1998). Factors that have been shown to control PNMT expression include cortisol and glucocorticoid receptors (Isobe et al 2000;Finotto et al 1999), the immediate early gene transcription factor Egr-1 (Isobe et al 2000), neural-crest associated developmental transcription factor, AP2 (Ebert et al 1998) and pituitary adenylate cyclase-activating polypeptide (Isobe et al 2003). An alteration in any of these factors may play a role in the variable PNMT expression levels that we describe in human phaeochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…This concurs with studies that have revealed low levels of PNMT mRNA expression in human phaeochromocytoma (Isobe et al 1998). Factors that have been shown to control PNMT expression include cortisol and glucocorticoid receptors (Isobe et al 2000;Finotto et al 1999), the immediate early gene transcription factor Egr-1 (Isobe et al 2000), neural-crest associated developmental transcription factor, AP2 (Ebert et al 1998) and pituitary adenylate cyclase-activating polypeptide (Isobe et al 2003). An alteration in any of these factors may play a role in the variable PNMT expression levels that we describe in human phaeochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…1A) upstream of the firefly luciferase reporter gene (pGL3RP893) were treated with varying concentrations of NGF up to 100 ng/ml, and PNMT promoter-driven luciferase reporter gene expression was de- (Ross et al, 1990;Ebert et al, 1994Ebert et al, , 1998Ebert and Wong, 1995;Wong et al, 1998;Her et al, 1999). B, transfected cells were treated with varying doses of NGF from 0 to 100 ng/ml, and luciferase activity was determined after 24 h. C, transfected cells were treated with 50 ng/ml NGF for times up to 24 h, and luciferase activity was determined.…”
Section: Ngf Activation Of the Pnmt Promotermentioning
confidence: 99%
“…For example, stimulation of the PNMT gene by the neural crest factor activating protein-2 (AP-2) requires a direct interaction with ligand-activated type II glucocorticoid receptors. 34 In addition, the PNMT gene contains overlapping consensus elements for the promoter selective transcription factor (Sp 1) and the immediate early gene transcription factor Egr-1 that are capable of differentially activating PNMT gene expression. 35 Sp 1, Egr-1 and the glucocorticoid receptor and AP-2 function cooperatively to stimulate PNMT promoter activity through poorly delineated mechanisms.…”
Section: Molecular Psychiatrymentioning
confidence: 99%